Comprehending Narrative Text: The Effectiveness of Cooperative Integrated Reading and Composition (CIRC) - Miftah Fariduddin; Firman Parlindungan (Ethical Lingua: Journal of Language Teaching and Literature, 2018)
The aim of this study was to investigate whether there was significant difference on the students’ reading comprehension of narrative text between those who were taught through Cooperative Integrated Reading and Composition (CIRC) method and those who were not. Forty-nine students were selected as the sample and quasi-experimental, non-randomized pre-test and post-test design were employed. The analysis of covariance showed that the students who were taught by using CIRC method statistically outperformed those who were not on their reading comprehension of narrative text, (F (1, 48) = 13.56, p < .05). This result implies that CIRC is an effective method to teach reading comprehension, particularly on narrative text. Since this study only focused on narrative text, future researchers might be interested to seek the effect of CIRC on other text genres. Similar study though may be conducted with a randomized design of larger population.